La fabrication de soi par la transformation matérielle - Thomas Marshall (Socio-anthropologie, 2017)
How a craft work may have effects both on the transformed material and on the person who experiences it? This article explores the hypothesis that the transformation activity of a material can have lasting effects on personal identity. Beyond the acquisition of professional skills, what does the work of interaction with the wood stimulate? What is left of it several years later? During professional learning, these effects occur more clearly because of their novelty. Through the analysis of excerpts from the narrative of life of two people of very different profile, appears retrospectively what played a significant role during their apprenticeship in carpentry-cabinetmaking. The technique of interview for explicitation of action (Vermersch, 2003), combined with an experiential preparation of research, has made it possible to bring out the richness of personal experience in the interaction with things.